Penerapan Fuzzy Logic untuk Sistem Pengendali Lalu Lintas - Deni Mulyadi; Eka Putra Pratama; Aries Saifudin; Yulianti Yulianti (Teknik Informatika Universitas Pamulang, 2021)
Fuzzy logic control is one application that has been able to provide a sulition for system traffic problem on higway. The funcition of the fuzzy logic control the speed of the vehicle. A traffic light system that is controlled by using a fuzzy logic control application to adjust trafic indicators to reduce congestion problem on the higway, because it takes too long to wait for the trafic light to trun green. To control traffic light, it requires tools called photoelectrik sensors at every intersection and an arduino mega 2560 microcontroller to run a fuzzy system into a programming language that can be accepted by hardware. And researching using a simulation of four intersection there must be at least 30 vehicles with a time of 60 seconds. The test results have proven changes in vehicles density at crossroads when the green lightis on.